Discovery of Penicillidmus in the Bismarck Archipelago, Papua New Guinea, with description of a new species from Lavongai (New Hanover) Island (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Penicillidmus Jałoszyński, 2014 was established to accommodate two Australian species of Glandulariini. Penicillidmus masseyensis Jałoszyński, 2014 and P. unicolor Jałoszyński, 2014 are known to occur in Cape York, northern Queensland. With the adult body length ranging from 0.83 to 0.86 mm, these species are among the smallest Australian scydmaenines. Another, yet undescribed species represented by a female, is also known to occur within the same area (Jałoszyński 2014). Penicillidmus resembles similarly small adults of Microscydmus Saulcy & Croissandeau, 1893, but can be easily distinguished on the basis of remarkable cephalic and prothoracic structures. Unlike any other Glandulariini, species of Penicillidmus have a unique system of carinae on the flattened ventral surface of the head, located posterior and lateral to the mouthparts. The submental carina runs along the anterior margin of the submentum and extends laterally along cardinal bases; the longitudinal lateral carina runs at each side of mouthparts and extends from the anterior margin of the head capsule to the ’neck’ region; and the transverse carina connects each longitudinal lateral carina with the mesoventral margin of the compound eye. Additionally, the apex of the terminal maxillary palpomere is thickened, and the pronotum bears a thick posterolateral brush of several long setae. The latter character is most easily observable; under a stereomicroscope the brush appears as a solid rod-like structure, individual setae can be recognized in transparent mounts under a compound microscope.